Pre-clinical investigation of brain mechanisms associated with Parkinson?s disease : the impact of diet - Nazario, Luiza Reali (2020)
Attempts are being made to find a cure or at least a better treatment that can slow down the progression of Parkinson?s disease, but recently, no intervention has been discovered. A better understanding of the basic mechanisms that underlie this disease is of great importance for the development of new drugs. Lifestyle factors, such diet, can influence different biological mechanisms involved in PD, such as the purinergic system, the dopaminergic system, neuroinflammation and microbiota. In this thesis, these factors will be explored in different animal models. In Chapter 2, the interaction of adenosine receptors with dopaminergic receptors and the potential role of adenosine receptor ligands in the treatment of PD are reviewed. In this chapter, the potential relation of adenosine with lifestyle and diabetes is discussed as well. In Chapter 3, we investigated the interaction of purinergic and dopaminergic receptors in a zebrafish model of PD. After intra-encephalic injection of 6-OHDA, zebrafish presented behavioral changes and slight effect on the dopaminergic system. In Chapter 4, we investigated the feasibility of in vivo PET imaging in living healthy adult zebrafish and in a zebrafish model of inflammation. This study demonstrated that in vivo PET imaging with 18F-FDG and 18F-NaF in living zebrafish is feasible and differences in uptake can be seen in a model of inflammation. In Chapter 5, we analyzed the impact of a cafeteria diet on the reward system in rats. Our study suggests that D2 receptors play a role in obesity and consumption of a cafeteria diet, but no alterations after challenge was observed. To elucidate the influence of a high fat diet (HFD) on PD progression, we investigated the effect of a HFD on the availability of D2 receptors and behavioral parameters in rats, in Chapter 6. The HFD aggravated the damage in the PD model, suggesting a detrimental role of the HFD on the onset or progression of PD. In Chapter 7, we suggest that the documented impact of HFD on neuroinflammation may be mediated by the gut microbiome in the 6-OHDA rat model of PD and it is independent of peripheral inflammation. The knowledge of the basic mechanisms underlying PD and their relationship with changes in lifestyle can help scientists to better understand the factors that trigger the onset of the disease and aid the development of new treatments and diagnostic tools. These studies can help reveal of the interaction between behavior, microbiota, dopaminergic and purinergic response, and inflammation in the gut and the brain.